Serum protein profile of hookworm infection in dogs. (November 2015) - Schmidt, Elizabeth; Rubio, Camila; Santos, Gisele; Barbosa, Luciano; Santos, Talita; Cezaro, Marcela
Abstract Hookworms are parasitic nematodes that cause anemia and intestinal infections in dogs, especially with large worm burdens. However, the serum protein profile of this parasitological disease is still poorly understood. The present study was design to evaluate 80 asymptomatic dogs (age; 8 months–2 years) to detect the presence of the hookworm thin-shelled, morulated eggs in faeces using faecal flotation and to evaluate the serum protein fractions determined by means of sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE). Forty dogs had an elevated quantity of eggs in faeces (+++) (PD) and 40 dogs were healthy (HD). Infected dogs showed significant increases for IgG estimated concentrations (PD 1.79 ± 0.8 g/dL and HD 1.44 ± 0.72 g/dL, p = 0.04), for ceruloplasmin estimated concentrations (PD 19 ± 15 mg/dL and HD 5 ± 3.5 mg/dL, p = 0.0001), for alpha 1-acid glycoprotein estimated concentrations (PD 31.4 ± 17.9 mg/dL and HD 13.5 ± 12.1 mg/dL, p = 0.0001) and for a non-identified protein of 23 kDa estimated concentrations (PD 641.5 ± 194.9 mg/dL and HD 519.8 ± 197.9 mg/dL, p = 0.007). Dogs with hookworm infection showed significant differences in the serum protein profile when compared to healthy animals.